The Relevance of the Voluntary Transfers of Federal Resources for the Consolidation of the Government’s Support Base in the Brazilian Congress - Rodrigues da Silva, Eduardo; Nunes, André (Revista del CLAD Reforma y Democracia, 2019)
The literature on coalition presidentialism in Brazil considers the allocation of federal resources to the electoral bases of parliamentarians as an available tool for the Presidency to obtain support for initiatives of its interest in the National Congress. This article aims to verify the relationship between the transfer of these resources, the voluntary transfers, and the support to the Government. Two groups of deputies were separated to find out this behavior: those that vote following the Government’s orientation and those that systematically vote against it. From each group a sample of 50 deputies was selected, from which the percentage of votes obtained in the 2014 elections in each municipality was inferred. The four municipalities in which a deputy reaches proportionately more votes belong to his electoral base. Crossing this base of municipalities with data on voluntary transfers from the Federal Government, statistical tests found that the volume of federal voluntary resources received by a given municipality is related to the supportive alignment of the mayor and the governor with the Federal Government and also with the institutional capacity of the municipality administration. However, the volume of transfers received cannot be explained by virtue of whether or not the municipality is the electoral base of a federal deputy aligned or facing opposition to the Federal Executive.